Recent trends in nanocomposite packaging films utilising waste generated biopolymers: Industrial symbiosis and its implication in sustainability - Zeba Tabassum; Anand Mohan; Narsimha Mamidi; Ajit Khosla; Anil Kumar; Pratima R. Solanki; Tabarak Malik; Madhuri Girdhar (IET Nanobiotechnology)
Abstract Uncontrolled waste generation and management difficulties are causing chaos in the ecosystem. Although it is vital to ease environmental pressures, right now there is no such practical strategy available for the treatment or utilisation of waste material. Because the Earth's resources are limited, a long‐term, sustainable, and sensible solution is necessary. Currently waste material has drawn a lot of attention as a renewable resource. Utilisation of residual biomass leftovers appears as a green and sustainable approach to lessen the waste burden on Earth while meeting the demand for bio‐based goods. Several biopolymers are available from renewable waste sources that have the potential to be used in a variety of industries for a wide range of applications. Natural and synthetic biopolymers have significant advantages over petroleum‐based polymers in terms of cost‐effectiveness, environmental friendliness, and user‐friendliness. Using waste as a raw material through industrial symbiosis should be taken into account as one of the strategies to achieve more economic and environmental value through inter‐firm collaboration on the path to a near‐zero waste society. This review extensively explores the different biopolymers which can be extracted from several waste material sources and that further have potential applications in food packaging industries to enhance the shelf life of perishables. This review‐based study also provides key insights into the different strategies and techniques that have been developed recently to extract biopolymers from different waste byproducts and their feasibility in practical applications for the food packaging business.